Company, its performance and perceived employer attractiveness - Musilová, Jana (2015)
This thesis analyses influencers of employer attractiveness with high focus on company performance and other elements concerning company as such. Theoretical part of this thesis aims to bring relevant background for the practical analysis. In particular, it examines areas such as talent management, employee value proposition and employer branding and their connection to employer attractiveness. Practical part identifies objective and subjective drivers of employer attractiveness. This part consists of three analyses: Questionnaire, Correlation Analysis and RPC Graduate Survey. Triangulation of all three analyses brings complex results concerning employer attractiveness influencers. Empirical part works towards answering of research questions and creating a recommendation manual that shall help companies to become attractive employers.